2021
DOI: 10.3390/polym13244328
|View full text |Cite
|
Sign up to set email alerts
|

Development of Application Specific Intelligent Framework for the Optimized Selection of Industrial Grade Magnetic Material

Abstract: This article attempts to introduce a simple and robust way for the classification of soft magnetic material by using multivariate statistics. The six magnetic properties including coercive magnetic field, relative magnetic permeability, electrical resistivity magnetic inductions, i.e., remanence and saturation along with Curie temperature are used for the classification of 16 soft magnetic materials. Descriptive statistics have been used for defining the prioritization order of the mentioned magnetic character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…It can be seen from Figure 7 that the corresponding factors for PC-1 are either polyethylene characteristics bands or the IR active region induced by fillers i.e., 440 cm −1 , 456 cm −1 , from 900–1200 cm −1 , 1210 cm −1 , 1596 cm −1 . PC-2 unveils the modifications because of irradiation, e.g., gamma irradiations results in an increase of –CH 2 stretching vibrations at 2849 and 2924 cm −1 [ 2 , 6 , 12 , 44 ], it is therefore, these two IR active bands have the positive loadings on PC-2 as shown in Figure 7 . In addition to this, edged Mg–OH stretching vibrations are also quantified by PC-2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be seen from Figure 7 that the corresponding factors for PC-1 are either polyethylene characteristics bands or the IR active region induced by fillers i.e., 440 cm −1 , 456 cm −1 , from 900–1200 cm −1 , 1210 cm −1 , 1596 cm −1 . PC-2 unveils the modifications because of irradiation, e.g., gamma irradiations results in an increase of –CH 2 stretching vibrations at 2849 and 2924 cm −1 [ 2 , 6 , 12 , 44 ], it is therefore, these two IR active bands have the positive loadings on PC-2 as shown in Figure 7 . In addition to this, edged Mg–OH stretching vibrations are also quantified by PC-2.…”
Section: Resultsmentioning
confidence: 99%
“…The diagonal of the 2nd quadrant indicated in Figure 9 shows a decrease in absorbance of filler’s IR active bands (in the region 900–1200 cm −1 ) and increase in absorbance of IR active bands associated to –CH 2 bending vibrations of long chain polyethylene at 1460 and 1470 cm −1 . This points toward the filler’s efficacy as free radical scavenger and enhancing the cross linking within the UHMWPE matrix because it is well established that radiation cross linking results in an increase in absorbance of CH 2 bending vibrations of long chain polyethylene [ 12 ]. The score plot of PCA shown in Figure 8 and Figure 9 confirmed that for the group of irradiated sample, samples irradiated with 65 and 100 kGy are the best ones, and for the group of UHMWPE/Mg-silicate, sample with 2.0% of Mg-silicate and irradiated with 25 kGy of gamma dose is the optimum choice, and UHMWPE/γMWCNTs composites containing 1.0% of γMWCNTs and irradiated with 25 kGy are the better choice among the existing alternatives in the group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the traffic density of a network grows, more cars will reach the optimal portion. Therefore, automobiles in the optimal sector rapidly distribute data packets [29,30]. Collisions in MAC layer packet transmission.…”
Section: An Example Of a Vanet In A Congestedmentioning
confidence: 99%
“…The free mixing energy [ 15 ] is used as a criterion to establish whether two polymers are compatible with one another. Both entropy and enthalpy may be thought of as kinds of energy that are present in the system.…”
Section: Introductionmentioning
confidence: 99%